GAMBARAN HISTOPATOLOGI HEPAR TIKUS PUTIH (Rattus norvegicus) JANTAN PASCA PEMBERIAN EKSTRAK INFUSA BUAH PARE (Momordica charantia L.) LOKAL NTT - Agnes Y Taek; Nemay A Ndaong; Cynthia D Gaina (Jurnal Veteriner Nusantara, 2020)
Hepatic is the largest gland in the body. Hepatic function in the metabolism and detoxification of a wide variety of compounds into the body. Infusion extract of bitter melon (M. charantia L.) fruit is a herbal preparation containing chemical compounds such as flavonoids, glycosides, triterpenoids, polyphenols, alkaloids, saponins, and tannins. Excessive drug dosing in a long period of time, can make liver damage acute, subacute or chronic. Toxic effects of drugs often seen in the tissues, especially the liver and kidneys are on histology, appearing as inflammatory cell infiltration, hidropic degeneration, fatty degeneration and necrosis. The purpose of this study is to determine the effect of variations in dose infusion extract of bitter melon fruit (M. charantia L.) locally NTT against white picture rat liver histopathology (R. norvegicus) male and determine the effective dose infusion extract of bitter melon fruit (M. charantia L.) NTT local who gave a response, or effects on fertility drugs white rat (R. norvegicus) male. The method used in this study is completely randomized design method namely by dividing the mice randomized into two treatment groups with different doses variations. Analysis of the data used is descriptive. The results obtained showed that the average infiltration in P1 was 5.8 ± 6.7, while the P2 is 3.7 ± 5.5. Hydropic degeneration in P1 was 17.3 ± 10.7 and in P2 was 63.5 ±32.7. fatty degeneration in P1 was 2.3 ± 4.4 and 10.2 ± At P2 is 9.5. Necrosis of P1 was 0.5 ± 0.8, while the P2 is 4.2 ± 2.9.